DEVELOPMENT OF STUDENT SCIENCE PROCESS SKILLS ASSESSMENT INSTRUMENTS ON ACID-BASE MATERIALS THROUGH INQUIRY-INTERNET OF THING (IIoT) - Nurdin, Muhamad Ali; Anwar, Dede Miftahul; Nuryantini, Ade Yeti; Farida, Ida (International Journal of Education, 2024)
This study aims to develop a test instrument for high school students' science process skills on acid-base solution material through Inquiry-Internet of Thing (IIoT). Science process skills are one of the skills that need to be mastered by students because it is the basis for students to have good analytical skills. Currently, the evaluation instrument for science process skills is only in the form of an observation sheet which sometimes provides a gap for teachers to assess students subjectively and has not been widely developed in acid-base materials. The indicators used in this instrument consist of nine indicators which are a combination of basic and integrated science process skills, while the method used in this research is the Research and Development (R D) method. The stages of developing this test instrument are making question indicators, making questions, judgment by material experts and evaluation experts, revising questions, testing, and revising questions. The questions developed were 18 questions in the form of multiple choice. The test developed has a high-reliability category (0.65), validity with a sufficient category (0.48), the level of difficulty, and the quality of the checkers that have not been balanced. 5 questions are suitable for use, 12 questions that need to be revised, and one question that needs to be replaced. The results of this study can be used to assist teachers in measuring students' science process skills and also develop them in other materials or lessons.